Adolescents’ autonomous functioning and implicit theories of ability as predictors of their school achievement and week-to-week study regulation and well-being - Mouratidis, Athanasios; Michou, Aikaterini; Vassiou, Aikaterini (Contemporary Educational PsychologyContemporary Educational Psychology, 2017)
Research on students’ motivation has mainly focused on interpersonal differences rather than on the ongoing, intrapersonal dynamics that forge students’ everyday life. In this five-month longitudinal (diary) study, we recruited a sample of 179 high school students from Greece (35.8% males; Mage = 16.27; SD = 1.02) to investigate through multilevel analyses the ongoing dynamics of students’ motivation. We did so by examining the relation between autonomous functioning and aspects of study regulation (namely, study efforts and procrastination) and well-being (namely, subjective vitality and depressive feelings). After controlling for perceived competence, we found week-to-week autonomous functioning to relate positively to study efforts and subjective vitality and negatively to procrastination and depressive feelings. Interestingly, implicit theories of ability - the degree to which one believes that ability is fixed or amenable - were found to moderate the week-to-week relations of autonomous functioning to study efforts and homework procrastination. In particular, autonomous functioning co-varied positively to study efforts and negatively to homework procrastination only among students who believed that ability is malleable. Also, beliefs that ability is fixed predicted poorer grades, lower mean levels of study efforts, and higher homework procrastination. The results underscore the necessity of taking a more dynamic view when studying motivational phenomena and the importance of jointly considering the implicit theory framework and self-determination theory.
Keywords: Academic achievement; diary study; Implicit theories; motivation; Self-determination; Students